The effectiveness of legal norms as a condition for the usefulness of legal impact (based on the norms of procedural law) - S.A. Kurochkin (Ученые записки Казанского университета: Серия Гуманитарные науки)
Legal norms constitute one of the key elements in the legal impact mechanism. Their effectiveness defines the usefulness of legal regulation in social relations. What are the main approaches to determining the effectiveness of legal norms, as well as to assessing and measuring it? How are the goals and results of legal norms related? The paper answers these and other questions. Using procedural law as an example, some proposals were made for practical application of methods for assessing the effectiveness of legal impact. It was concluded that the effectiveness of procedural law norms can be determined by identifying the circumstances associated with them: the process of law enforcement in courts; specific features of legal awareness and behavior of subjects, who are not endowed with authority and may either observe the requirements established by procedural law norms or flout them. Taken together, all these circumstances define the effectiveness of procedural law norms applied for settlement of problems in legal relations arising while hearing civil cases in courts.